Evaluación de Injerto por yemas en cuatro variedades de cítricos utilizando como patrón el limón real (Citrus limon) en la zona Babahoyo - Cruz Silva, Leonardo Enrique (2025)
In Ecuador, lemon is an ancient crop in its traditional form. Its use and culinary applications vary depending on the production region, and it has a variety of uses that have not yet been fully explored or exploited. For this reason, the present study aims to evaluate bud grafting in four citrus varieties and their compatibility using the royal lemon (Citrus limon) as a rootstock for the areas of the city of Babahoyo. The methodology will be carried out through the use of experimental statistics; it consisted of four treatments in five repetitions, with the Tukey test at 95% probability. 15 plants were obtained in total for each treatment; The population of this research is composed of all the royal lemon rootstocks that were bud grafted using 4 citrus varieties: Valencia orange, red grapefruit, king mandarin and tangelo orange; the data to be evaluated are: percentage of take (PP), number of leaves, stem diameter, shoot height, leaf area, number of shoots and shoot vigor, this evaluated in a period of 60, 90 and 120 days. The main focus of this study will be on: Evaluating Bud Grafting in four different types of citrus using the genuine lemon as a rootstock. The results showed that the red grapefruit is the citrus that maintains the greatest increase in the number of leaves, as demonstrated by the compilation of results where it indicates that the average number of leaves in 60 days is 42.3, 90 days is 45.7 and 49.6 leaves in 120 days. It is concluded that the initial growth of the grafts is that in the Valencia orange citrus it has a growth of 2.8 mm, the red grapefruit citrus the stem diameter grows 4.2 mm, the mandarin king citrus the stem grows 2.5 mm and the tanjelo orange stem grows 2.3 mm in an initial period of 60 days.